Improving Students’ Enrolment in Physical Education in Senior Secondary Schools through Available Prospects and Career Opportunities in Enugu State: An Expert-Based Cross-Sectional Survey - Omeje, Faith Chidinma; Chukwudo, Donatus Udochukwu; Ugwueze, Fabian Chibunine (International Journal of Human Kinetics, Health and Education, 2023)
This study focused on improving students’ enrolment in physical education in senior secondary schools through available prospects and career opportunities in Enugu State. It was an expert-based cross-sectional survey conducted in Enugu State, Nigeria. The population for the study comprised 58 PE experts with minimum of master’s degree qualification, currently working as academic staff in tertiary institutions. Using a purposive sampling technique, 50 experts were sampled and surveyed. A researcher-designed self-administered instrument titled “Students’ Enrolment in Physical Education Questionnaire - SEPEQ” with a reliability index of .91 was used for data collection. Mean scores and standard deviation were used to answer the research question, while independent t-test statistics was adopted in testing the null hypothesis at p≤.05. The findings indicated that overall, PE experts considered the proposed strategies such as: organizing routine seminars for all students in the junior secondary school level with strong emphasis on educating them on the available prospects and career opportunities in PE by the school authority, appropriate for improving students’ understanding of available prospects and career opportunities in PE (=3.53; SD=.57). There was no significant difference in improving students’ enrolment in PE in secondary schools through available prospects and career opportunities based on experts’ socio-demographic characteristics (gender, educational qualification, and work experience - p>.05). In conclusion, the experts considered organizing routine seminars for all students in the junior secondary school level with strong emphasis on educating them on the available prospects and career opportunities in PE by the school authority among others appropriate. No significant difference was recorded on the appropriateness of the strategies based on socio-demographic variables. Therefore, the need for educational institutions to adopt the validated strategies for improving students’ enrolment in PE in SSS becomes very essential.